Quality of care in the last year of life: adaptation and validation of the German “Views of Informal Carers’ Evaluation of Services - Last Year of Life - Cologne” - Dust, Gloria; Schippel, Nicolas; Stock, Stephanie; Strupp, Julia; Voltz, Raymond; Rietz, Christian (BMC health services research, 2022)
To inform quality improvement and strengthen services provided in the last year of life, measuring quality of care is essential. For Germany, data on care experiences in the last year of life that go beyond diagnoses and care settings are still rare. The aim of this study was to develop and validate a German version of the ‘Views of Informal Carers’ Evaluation of Services - Short Form (VOICES-SF)’ suitable to assess the quality of care and services received across settings and healthcare providers in the German setting in the last year of life (VOICES-LYOL-Cologne).
Gesehen am 07.11.2023